1999
DOI: 10.1007/bf03161751
|View full text |Cite
|
Sign up to set email alerts
|

Response of invertebrates to glyphosate-induced habitat alterations in wetlands

Abstract: Wetlands in the Prairie Pothole Region of eastern North Dakota, USA are often overgrown with cattails (Typha spp), providing habitat for crop-depredating blackbirds and impeding use by waterfowl. One and two years post-treatment (1992 and 1993), we assessed the response of invertebrates to a catastrophic reduction in cattail coverage caused by glyphosate, a herbicide apptied to about 14,000 ha of North Dakota's wetlands since 1991. Numbers of Crustacea, Hydracarina, O1igochaeta, Copepoda, Ostracoda, and Cladoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
5
24
2
Order By: Relevance
“…There was, however, a negative relationship between chironomid emergence rates and plant cover across all treated sides of wetlands in August 2009, suggesting that the loss of macrophytes from herbicide treatments led to increased chironomid abundance, possibly through some intermediary mechanism such as a loss of predators or increased food amounts. These results concur with another study that found higher emergence rates of chironomids after removal of macrophytes with a glyphosate-based herbicide [15].…”
Section: Discussionsupporting
confidence: 92%
“…There was, however, a negative relationship between chironomid emergence rates and plant cover across all treated sides of wetlands in August 2009, suggesting that the loss of macrophytes from herbicide treatments led to increased chironomid abundance, possibly through some intermediary mechanism such as a loss of predators or increased food amounts. These results concur with another study that found higher emergence rates of chironomids after removal of macrophytes with a glyphosate-based herbicide [15].…”
Section: Discussionsupporting
confidence: 92%
“…Many herbicides used in forestry and agriculture have been tested for effects on biota in streams but rarely in wetlands. Linz et al [36] examined the effects of glyphosate in prairie pothole wetlands. They found a significant increase in macroinvertebrate and chironomid abundance in treated wetlands and suggested that this was an indirect effect caused by increased food resources resulting from cattails ( Typha spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Populations of some aquatic invertebrates were also enhanced by a reduction in cattail (reedmace -Typha spp.) cover with glyphosate-based herbicide (Linz et al 1999).…”
Section: Unwanted Especially Exotic Speciesmentioning
confidence: 99%